Regional economic resilience and sustainable development: Does industrial diversity matter? - Shangzhi Mu (PLoS ONE, 2026)
Regional sustainable development is a fundamental pathway toward achieving long-term economic stability, social equity, and ecological balance. Particularly in the face of unexpected shocks and systemic risks, economic resilience plays a critical role in ensuring the attainment of sustainability goals. Drawing on endogenous growth theory and dynamic capabilities theory, this study focuses on 31 provincial-level administrative divisions in mainland China as the target regions, utilizing panel data from 2004 to 2023 to empirically examine the relationships. The baseline regression results indicate a significant positive effect of economic resilience on sustainable development. Moderation analysis further reveals that industrial diversification, human capital, and environmental regulation significantly enhance the positive impact of resilience. Mediation tests show that economic resilience promotes sustainable development indirectly by improving the level of marketization. Heterogeneity analysis confirms that the impact of economic resilience on sustainable development varies significantly across regions. The findings of this study provide a scientific basis for governments to formulate more effective risk-mitigation policies and for firms to identify more stable regions for investment.